The Effects of a Low Glutamate Dietary Intervention on Anxiety and PTSD in Veterans with Gulf War Illness (FS15-08-19). (13th June 2019) - Brandley, Elizabeth; Kirkland, Anna; Sarlo, Gabrielle; VanMeter, John; Baraniuk, James; Holton, Kathleen
Abstract: Objectives: Glutamate is an amino acid and also serves as the most ubiquitous neurotransmitter in the human body. Previous work has shown that dysregulated glutamatergic neurotransmission is implicated in the etiology of anxiety disorders. Objective: To examine the effect of a low glutamate dietary intervention on anxiety and Posttraumatic Stress Disorder (PTSD) in veterans with Gulf War Illness (GWI). Methods: Forty veterans with GWI are being recruited for a randomized-controlled clinical trial testing the effects of a low glutamate diet on neurological symptoms. After consent, subjects complete baseline measures, then subjects are randomized to the low-glutamate diet or a wait-listed control group. For the active intervention phase, they follow a 1-month low glutamate diet and then are re-tested prior to entering a double-blind, placebo-controlled crossover challenge with monosodium glutamate (MSG) or placebo, to test for return of symptoms. Preliminary data are presented here for changes observed on the Generalized Anxiety Disorder 7-item (GAD-7) scale and the PTSD Checklist (PCL-C) after one month on the diet in subjects recruited to date. Pre-post diet scores were compared for anxiety and PTSD using a Wilcoxon Signed Rank test in SAS. Results: Seventeen veterans (M = 15; F = 2) with GWI have been recruited to date (mean age = 50 ± 4 yrs). Preliminary analyses demonstrate that after one month on the diet, significant improvements were noted for anxiety (score reduced from a median (IQ range) of 9 (13) to 5 (10), p = 0.01) and for PTSD (median (IQ) score reduced from 58 (33) to 43 (28), p = 0.04). Conclusions: This study suggests that consuming a low glutamate diet may improve anxiety and PTSD in veterans suffering from Gulf War Illness. More research is needed to further explore the role of dietary glutamate in anxiety disorders. Funding Sources: U.S. Army Medical Research Acquisition Activity, 820 Chandler Street, Fort Detrick MD 21702-5014 is the awarding and administering acquisition office. This work was supported by the Office of the Assistant Secretary of Defense for Health Affairs, through the Gulf War Illness Research Program under Award No. W81XWH-17-1-0457 . Opinions, interpretations, conclusions and recommendations are those of the author and are not necessarily endorsed by the Department of Defense.